2016
DOI: 10.1007/s13318-016-0346-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for Treating ADHD: A Naturalistic Clinical Study of Methylphenidate Blood Concentrations in Children and Adults With Optimized Dosage

Abstract: BackgroundMethylphenidate (MPH), along with behavioral and psychosocial interventions, is the first-line medication to treat attention-deficit hyperactivity disorder (ADHD) in Sweden. The dose of MPH for good symptom control differs between patients. However, studies of MPH concentration measurement in ADHD treatment are limited.ObjectiveTo describe blood and oral fluid (OF) concentrations of MPH after administration of medication in patients with well-adjusted MPH treatment for ADHD, and to identify the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…In our study, we found a slightly lower correlation between methylphenidate concentrations in oral fluid and plasma (r = 0.61). Our data are in line with studies in patients showing three-to-four-fold higher methylphenidate concentrations in oral fluid than in blood, while the opposite was true for ritalinic acid [33,34]. The present study indicates that oral fluid may serve as an alternative non-invasive matrix to assess medication adherence, as the oral fluid concentrations of dl-threo-methylphenidate in our study roughly reflected d-threo-methylphenidate concentrations in plasma.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found a slightly lower correlation between methylphenidate concentrations in oral fluid and plasma (r = 0.61). Our data are in line with studies in patients showing three-to-four-fold higher methylphenidate concentrations in oral fluid than in blood, while the opposite was true for ritalinic acid [33,34]. The present study indicates that oral fluid may serve as an alternative non-invasive matrix to assess medication adherence, as the oral fluid concentrations of dl-threo-methylphenidate in our study roughly reflected d-threo-methylphenidate concentrations in plasma.…”
Section: Discussionsupporting
confidence: 91%
“…Reportedly, a dose–response relationship was observed with osmotic-controlled release oral delivery system methylphenidate (OROS-MPH) in children with combined-type ADHD, whereas such a relationship was not noted in children with ADHD of a predominantly inattentive subtype 37. Furthermore, the association between dose optimization and weight remains inconclusive; some studies have reported no relationship between the final optimal dose and body weight, while others have indicated weight as a reliable clinical parameter for dose optimization 3840. Douglas et al reported a linear dose–response relationship between dose (0.15, 0.30, and 0.60 mg/kg) and improvements in performance 41.…”
Section: Dose Optimization In Clinical Practicementioning
confidence: 99%
“…The need for multiple doses of MPH to achieve effective symptom control further highlights the importance of an individualized or tailored treatment approach for ADHD. Recently, Chermá et al40 reported a large variation in the optimal treatment dose of 59 patients with ADHD; however, blood sample analysis revealed that the median daily dose per body weight was similar (~1.0 mg/kg). As per the available literature, genetic differences may lead to significant variability in pharmacokinetic profiles across the day at an individual level, which may result in the large variation observed 58…”
Section: Dose Optimization In Clinical Trials and Naturalistic Studiesmentioning
confidence: 99%
“…On the other hand, this limitation would not differ between the studied groups. More importantly, we did not have information on further phenotypic characteristics, and here bodyweight is the most important factor as it affect doses of methylphenidate prescribed [ 35 ]. Further, we did not study other simultaneous pharmacological treatments, which may affect doses and type of ADHD medications prescribed.…”
Section: Discussionmentioning
confidence: 99%